ANALYSIS OF SCHOOL LITERACY POLICIES IN THE FACE OF THE SOCIETY ERA 5.0 - Ilmiah Nafhah Karimah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
Industry 4.0, also known as the disruptive period, stresses increasing efforts to place humans at the center of innovation (human-centered) while technical developments are used to improve the quality of life, social responsibility, and sustainability in all disciplines, including education. In light of the 5.0 social media age, the purpose of this study is to examine school literacy policies. This study uses qualitative analysis in conjunction with a library study and the Society 5.0 concept approach to literacy policy. Journals, articles, books, and other pertinent references were used as data sources for this study. Using library studies and documentation, data collection strategies are used. The findings revealed that in the period of society 5.0, literacy policies based on old literacy (basic literacy) must be replaced with new literacy based on the internet, technology, and social media.